Design of a Web-Based Visiting Service System for Inmates at the Class IIA Binjai Correctional Facility - Rahmah, Siti; Barani Fachri; Hendry (Cattleya Darmaya Fortuna, 2026)
This study aims to design and develop a web-based inmate visiting service system at the Class IIA Binjai Correctional Facility to improve efficiency, transparency, and accessibility for the public. The research method includes system requirements analysis, structured design approach, and implementation using web technologies that enable online visit registration. The system is designed to minimize queues, reduce administrative errors, and provide real-time visiting schedule information for both visitors and officers. The results of this study indicate that the developed system is capable of enhancing the quality of visiting services, accelerating administrative processes, and supporting more integrated and secure data management within the correctional facility environment.